Effects of e-cigarettes on oral health: chemical components and oral manifestations. Literature review - Sánchez Barbecho , Bryam Jonnathan (2025)
The global use of electronic cigarettes has increased considerably as an alternative to tobacco; however, their effects on oral health remain uncertain, raising concerns within the scientific community. The aim of this study is to analyze the impact of the chemical components of electronic cigarettes on oral health by evaluating their potential adverse effects and identifying the main oral conditions associated with their use. A narrative, descriptive literature review was conducted. A total of 67 articles were retrieved from PubMed, 28 from Google Scholar, and 8 from SciELO, resulting in an initial total of 103 articles from the last 5 years, published in Spanish and English. Ultimately, 30 relevant articles were selected. The keywords used included "Electronic Cigarettes", "Oral Health", "Nicotine", "Propylene Glycol", and "Flavoring Agents". The review confirmed that the main chemical components of electronic cigarettes are propylene glycol, vegetable glycerin, nicotine, and flavorings. These substances are associated with oral problems such as xerostomia, periodontal disease, dental caries, and lesions in the oral mucosa. This study calls for a reconsideration of the perceived safety of e-cigarettes and emphasizes the need for stronger education and regulation regarding their use. The findings highlight the urgent need for more extensive research on their long-term effects on oral health.